The human CAS protein which is homologous to the CSE1 yeast chromosome segregation gene product is associated with microtubules and mitotic spindle. - Scherf, U (1996)
Human CAS cDNA contains a 971-aa open reading frame that is homologous to the essential yeast gene CSE1. CSE1 is involved in chromosome segregation and is necessary for B-type cyclin degradation in mitosis. Using antibodies to CAS, it was shown that CAS levels are high in proliferating and low in nonproliferating cells. Here we describe the distribution of CAS in cells and tissues analyzed with antibodies against CAS. CAS is an approximately 100-kDa protein present in the cytoplasm of proliferating cells at levels between 2 x 10(5) and 1 x 10(6) molecules per cell. The intracellular distribution of CAS resembles that of tubulin. In interphase cells, anti-CAS antibody shows microtubule-like patterns and in mitotic cells it labels the mitotic spindle. CAS is removed from microtubules by mild detergent treatment (cytoskeleton preparations) and in vincristine- or taxol-treated cells. CAS is diffusely distributed in the cytoplasm with only traces present in tubulin paracrystals or bundles. Thus, CAS appears to be associated with but not to be an integral part of microtubules. Immunohistochemical staining of frozen tissues shows elevated amounts of CAS in proliferating cells such as testicular spermatogonia and cells in the basal layer cells of the colon. CAS was also concentrated in the respiratory epithelium of the trachea and in axons and Purkinje cells in the cerebellum. These cells contain many microtubules. The cellular location of CAS is consistent with an important role in cell division as well as in ciliary movement and vesicular transport.